Correlation between serum carnosinase concentration and renal damage in diabetic nephropathy patients - Zhou, Zhou; Liu, Xue-qi; Zhang, Shi-qi; Qi, Xiang-ming; Zhang, Qiu; Yard, Benito A.; Wu, Yong-gui (Amino acids, 2021)
Diabetic nephropathy (DN) is one of the major complications of diabetes and contributes significantly towards end-stage renal disease. Previous studies have identified the gene encoding carnosinase (CN-1) as a predisposing factor for DN. Despite this fact, the relationship of the level of serum CN-1 and the progression of DN remains uninvestigated. Thus, the proposed study focused on clarifying the relationship among serum CN-1, indicators of renal function and tissue injury, and the progression of DN. A total of 14 patients with minimal changes disease (MCD) and 37 patients with DN were enrolled in the study. Additionally, 20 healthy volunteers were recruited as control. Further, DN patients were classified according to urinary albumin excretion rate into two groups: DN with microalbuminuria (n = 11) and DN with macroalbuminuria (n = 26). Clinical indicators including urinary protein components, serum carnosine concentration, serum CN-1 concentration and activity, and renal biopsy tissue injury indexes were included for analyzation. The serum CN-1 concentration and activity were observed to be the highest, but the serum carnosine concentration was the lowest in DN macroalbuminuria group. Moreover, within DN group, the concentration of serum CN-1 was positively correlated with uric acid (UA, r = 0.376, p = 0.026) and serum creatinine (SCr, r = 0.399, p = 0.018) and negatively correlated with serum albumin (Alb, r = − 0.348, p = 0.041) and estimated glomerular filtration rate (eGRF, r = − 0.432, p = 0.010). Furthermore, the concentration of serum CN-1 was discovered to be positively correlated with indicators including 24-h urinary protein-creatinine ratio (24 h-U-PRO/CRE, r = 0.528, p = 0.001), urinary albumin-to-creatinine ratio (Alb/CRE, r = 0.671, p = 0.000), urinary transferrin (TRF, r = 0.658, p = 0.000), retinol-binding protein (RBP, r = 0.523, p = 0.001), N-acetyl-glycosaminidase (NAG, r = 0.381, p = 0.024), immunoglobulin G (IgG, r = 0.522, p = 0.001), cystatin C (Cys-C, r = 0.539, p = 0.001), beta-2-microglobulin (β2-MG, r = 0.437, p = 0.009), and alpha-1-macroglobulin (α1-MG, r = 0.480, p = 0.004). Besides, in DN with macroalbuminuria group, serum CN-1 also showed a positive correlation with indicators of fibrosis, oxidative stress, and renal tubular injury. Taken together, our data suggested that the level of CN-1 was increased as clinical DN progressed. Thus, the level of serum CN-1 might be an important character during the occurrence and progression of DN. Our study will contribute significantly to future studies focused on dissecting the underlying mechanism of DN.